Polymorphisms in TP53, MDM2 Genes and Risk of Renal Cell Carcinoma in a Mongolian Population (Central Asian Journal of Medical Sciences, 2025)
Objective: Renal cell carcinoma (RCC) is one of the most common malignancies of the kidney, with genetic factors playing a critical role in its development. Among the key genetic factors, TP53 and MDM2 gene polymorphisms have been implicated in cancer susceptibility, but their association with RCC remains unclear in different populations. This study evaluated the association of TP53 and MDM2 gene polymorphisms with RCC risk among Mongolian individuals. Method: In a hospital-based case-control study, 88 RCC cases and 88 matched controls were analyzed for TP53 and MDM2 variants using RFLP-PCR based genotyping. Results: The TP53 CG and CC genotypes and MDM2 TG and GG genotypes were not significantly associated with RCC risk when considered individually. However, individuals carrying the MDM2 GG and TP53 CC genotypes showed elevated RCC risk, although statistical significance was not reached. No strong interaction effects between genotypes and clinical risk factors such as smoking or urinary tract disease were observed. Conclusion: While TP53 and MDM2 polymorphisms showed trends toward association with RCC, larger studies are warranted to clarify their roles in genetic susceptibility within the Mongolian population.